2020
DOI: 10.3390/microorganisms8040548
|View full text |Cite
|
Sign up to set email alerts
|

SpoVG Is Necessary for Sporulation in Bacillus anthracis

Abstract: The Bacillus anthracis spore constitutes the infectious form of the bacterium, and sporulation is an important process in the organism’s life cycle. Herein, we show that disruption of SpoVG resulted in defective B. anthracis sporulation. Confocal microscopy demonstrated that a ΔspoVG mutant could not form an asymmetric septum, the first morphological change observed during sporulation. Moreover, levels of spoIIE mRNA were reduced in the spoVG mutant, as demonstrated using β-galactosidase activity assays. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…Further, we determined the spore yield ratio and found Δ spoVG mutant could not produce mature spores (Table S2 ). Our results were quite in accord with recent report of Chen et al [ 4 ] that in Bacillus anthracis , whose spoVG deletion mutant completely lost sporulation ability and it could not form an asymmetric septum. Therefore, it was concluded that SpoVG protein may play an important role in regulating sporulation of B. cereus 0–9.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, we determined the spore yield ratio and found Δ spoVG mutant could not produce mature spores (Table S2 ). Our results were quite in accord with recent report of Chen et al [ 4 ] that in Bacillus anthracis , whose spoVG deletion mutant completely lost sporulation ability and it could not form an asymmetric septum. Therefore, it was concluded that SpoVG protein may play an important role in regulating sporulation of B. cereus 0–9.…”
Section: Resultsmentioning
confidence: 99%
“…Sporulation of B. subtilis has been divided into so-called “stages” 0 to VII using electron microscopy. In the B. cereus group (which includes Bacillus anthracis ), sporulation is comparable to that in B. subtilis , but there are some differences between different strains [ 4 ]. For example, spore-coat assembly begins at the mother-cell-proximal pole of the forespore in B. subtilis , whereas coat material first appears on the long axis of the forespore in B. anthracis and B. cereus [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SpoVG is also involved in haemolytic activity caused by B. subtilis [119]. Recently, it was also shown to be essential for the formation of B. anthracis spores, which consist the infectious form of this bacterium [118]. The absence of SpoVG completely impaired its sporulation capabilities, with the inhibition occurring before the asymmetric division step, indicating that the B. anthracis SpoVG has a different role than it does in B. subtilis [118].…”
Section: The Role Of Atypical Rna-binding Proteins Regulating Adaptive Responses In Gram-positive Bacteriamentioning
confidence: 99%
“…B. anthracis is the causative agent of anthrax and can manifest in four ways, namely: cutaneous, inhalation, gastrointestinal or injectable (Hagan et al, 2018;Chen et al, 2020). B. cereus causes foodborne diseases, such as gastrointestinal, diarrhea and emesis (Yu et al, 2019;Huang et al, 2020).…”
Section: Gram-positive Bacillimentioning
confidence: 99%